Advanced Social Media Marketing How to Lead, Launch, and Manage a Successful Social Media Program - Funk, Tom. (Apress : Imprint: Apress, 2013)
Hundreds of millions of Americans are using social media (SM), and already some 70% of businesses have joined them there, using Facebook and other SM platforms to connect with their customers, and attract new ones. So the real question isnỚ"t whether to take your business onto social media platformsỚ but how to do it quickly, effectively, on a budget, with smart goals, and a road map for success.℗ Advanced Social Media Marketing:℗ How to Lead, Launch, and Manage a Successful Social Media Program cuts through the hype and fluff about how social media is changing the world, and it gets down to what really matters: How you as a manager can best use SM to benefit your business. Written by a veteran online marketer and ecommerce professional, the book shares practical strategies and tactics to let you launch and scale a successful corporate social media program.℗ ℗ Advanced Social Media Marketing:℗ How to Lead, Launch, and Manage a Successful Social Media Program℗ is for the manager who already knows something about social media and wants to roll up his or her sleeves and get down to business. In it, we simplify tasks that might otherwise be complicatedỚ like adopting and tracking key performance metrics, developing online ad campaigns, or creating Facebook apps like games, giveaways and sweepstakes with the capacity to go viral.℗ Businesses can harness the unique advantages of this new medium, but they need a practical, no-nonsense guide like this one. Otherwise they risk being ignored, wasting time and money or, even worse, damaging their own brand and seeing a well-intentioned online program blow up.℗ ℗ ℗ The book is heavy on the how-to, case studies, campaign results and other statistics, and interviews with℗ ecommerce managers at℗ businesses large and small. It also includes the authorỚ"s own experiences at Green Mountain Coffee Roasters, Wine of the Month Club, and others.℗ While this book will be accessible enough for someone implementing a social media program for the first time, itỚ"s ambitious enough to benefit experienced SM hands who are looking for good ideas and techniques to push their online community to the next level of size, interactivity, and buzz.℗ ℗ .